Why Governments Should Stop Non-Social Subsidies : Measuring Their Consequences for Rural Latin America - López, Ramón (World Bank, Washington, DC, 2012)
The provision of public goods and the amelioration of market failure are the classical justifications for government intervention in the economy. In reality, (1) governments intervene in markets that are not affected by failure, and (2) a large share of the government resources is spent in private goods, not in public goods. In contrast to issue 1, issue 2 has received little attention in the literature, in spite of the potentially large efficiency and equity losses arising from misguided allocations of public expenditures. López empirically documents the size of (2) in the rural sector and investigates its consequences for rural development for 10 Latin American countries over the 1985-2000 period. The econometric evidence suggests that the structure of public expenditures is an important factor of economic development in the rural sector, much greater than that of the level of public expenditures and of other factors on which the development literature has traditionally focused. Expanding total public expenditure in rural areas while maintaining the existing public expenditure composition prevailing in certain countries does little to promote agricultural income and reduce rural poverty. Spending a significant share of government resources in (non-social) subsidies causes less agriculture income, induces an excessive reliance of agriculture on land expansion, and reduces the income of the rural poor.